Measuring the electrical charge and settling velocity of volcanic ash with a new, cost-effective apparatus (VoltAsh) both in the laboratory and in the field - Allan Fries; Eduardo Rossi; Jonathan P. Merrison; Jens Jacob Iversen; Tatsushi Matsuyama; Frédéric Arlaud; Jonathan Lemus; Simon Thivet; Carolina Diaz-Vecino; Riccardo Simionato; Costanza Bonadonna (Bulletin of Volcanology, 2026)
Electrical charges play a key role in particle-particle interactions during transport and deposition of volcanic ash with significant impact on their atmospheric residence time, as they can influence aggregation processes. Nonetheless, direct field measurements are rare due to logistic challenges, resulting in a very limited understanding of charge generation and aggregation mechanisms. This study introduces VoltAsh, a cost-effective, portable device for measuring the charge and velocity of settling volcanic ash particles using a Through-Type Faraday Cage (TTFC) and a charge amplifier circuit. Laboratory validation confirmed the accuracy of both charge and velocity measurements when compared with state-of-the-art techniques. Field deployments at Sakurajima volcano (Japan) in November 2023 enabled automated, semi-continuous measurements over several hours, detecting particle charges ranging from 0.5 to 250 pC and velocities up to 5 ms $$^{-1}$$ - 1 . Measurements at Etna volcano (Italy) in July 2024 detected fewer charged particles, likely due to differences in eruptive style, grain size, particle properties and atmospheric conditions. These findings highlight VoltAsh’s potential for advancing studies of volcanic ash transport and deposition processes.